Machining method for top cover with integrally-formed anti-explosion valve

Through the top cover processing method of stamping and short-term annealing, the problems of uneven hardness and unstable blasting pressure caused by material recrystallization in the preparation of explosion-proof valve top cover are solved, and the effects of process simplification, cost saving and blasting pressure stability are achieved.

CN119216999APending Publication Date: 2024-12-31ZHEJIANG ZHONGZE PRECISION TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411507909.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the top cover preparation process of the existing secondary battery explosion-proof valve, the split structure requires separate equipment and a high-cost processing process. The traditional integrated explosion-proof valve recrystallizes the material after stamping, resulting in uneven hardness, affecting the stability of the blasting pressure.

Method used

A method of top cover processing with integrated molding of explosion-proof valves is controlled by stamping, cleaning and short-term annealing treatment, and the annealing temperature is controlled at 300-400℃ and the time is 10-120 seconds to avoid the re-crystallization of the whole material and maintain the top cover. Strength to improve material structure uniformity in the marking area.

Benefits of technology

It reduces processes, reduces costs, improves production efficiency, stabilizes the blasting pressure value, avoids the risk of brittle cracking of materials, and meets the battery safe use requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119216999A_ABST
    Figure CN119216999A_ABST
Patent Text Reader

Abstract

The invention provides a machining method for a top cover with an integrally-formed anti-explosion valve. The machining method sequentially comprises the following steps that S1, raw materials of the top cover are prepared; s2, stamping on one surface of the top cover through stamping equipment to form a circle of indented explosion-proof valve; s3, the top cover semi-finished product with the anti-explosion valve is cleaned through cleaning equipment; and S4, the cleaned semi-finished top cover is subjected to short-time annealing treatment through annealing equipment. Through short-time annealing treatment, the materials at the nicks can be recrystallized and softened, the structure is more uniform, the structures of other parts of the top cover are kept unchanged, and the bursting pressure value is reduced and more stable on the premise that the overall strength of the top cover is not changed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for processing a top cover with an integrally formed explosion-proof valve. Background Art

[0002] The main function of the explosion-proof valve of the secondary battery is: when abnormal conditions such as thermal runaway occur inside the battery, the internal pressure of the battery cell increases rapidly. The explosion-proof valve can be opened and released in time when the battery cell as a whole expands uncontrollably or even explodes, reducing the consequences of accidents such as fire and explosion of the battery, and ensuring personal and property safety. Therefore, the explosion-proof valve plays a very important role in the safe operation of the battery cell.

[0003] Most of the top covers of secondary batteries in the prior art are made by the manufacturing process of explosion-proof valve split structure (such as Figure 1 As shown in the figure, an explosion-proof valve made of special aluminum material is laser welded on the stamped top cover. This assembly method requires separate equipment and processing to prepare the explosion-proof valve, and the cost is relatively high. The material of the separate explosion-proof valve is also a special material, and only a few manufacturers can manufacture this material. In addition, this material contains a high content of Fe, and the precipitation of Fe has an adverse effect on the life and safety of the battery cell. Moreover, the traditional single explosion-proof valve will be annealed after stamping, and the material will recrystallize and soften, and then it will be welded to the stamped top cover, which involves many steps, low production efficiency, and high cost. Therefore, the integrated structural design of the explosion-proof valve and the top cover can effectively solve the above problems.

[0004] For example: Chinese invention patents CN115377574A and CN116073042A both disclose the integrated stamping process of the top cover and the explosion-proof valve, focusing on the stamping of the material strip in the mold, the explosion-proof valve, and the stamping method of the explosion-proof valve safety notch. The integrated explosion-proof valve top cover will cause a large and uneven deformation ratio of the material during the stamping process, thereby forming an elongated fiber structure. This problem will lead to uneven material structure and excessive hardness at the explosion-proof valve safety notch, which will cause uneven strength at the notch and the risk of brittle cracking of the material, and ultimately result in unstable bursting pressure values.

[0005] For another example, Chinese invention patent CN116765208A discloses a preparation method for integrally forming a cover plate and an explosion-proof valve, comprising the following steps: stamping, punching a light cover plate to form an explosion-proof valve by a stamping device; cleaning, cleaning the cover plate and the explosion-proof valve by a cleaning device; and annealing, adjusting the temperature of the annealing furnace to a preset temperature, placing the cover plate in the annealing furnace for insulation, the temperature of the annealing furnace is 330℃-370℃, and the insulation time is at least 30min. However, in Chinese invention patent CN116765208A, the cover plate is subjected to an overall annealing treatment, the temperature of the annealing furnace is 330℃-370℃, and the insulation time is at least 30min, which will cause the entire cover plate material to recrystallize and soften, reduce the overall strength of the cover plate, and make it difficult to meet the use requirements. At present, the production of cover plates in the battery structural parts industry does not undergo annealing treatment. Summary of the invention

[0006] The purpose of the present invention is to overcome the above-mentioned shortcomings in the prior art and provide a method for processing a top cover with an integrally formed explosion-proof valve. Through a short-time annealing treatment, the material in the notched area of ​​the explosion-proof valve is recrystallized to form a recrystallized structure to reduce the material strength in the notched area and improve the plasticity at the notched area, thereby achieving the effect of stabilizing the bursting pressure of the explosion-proof valve. Through the short-time annealing, the material of the cover plate does not undergo recrystallization and softening, and the original strength is maintained unchanged, meeting the actual use requirements.

[0007] The technical solution adopted by the embodiment of the present invention to solve the above-mentioned problem is: a method for processing a top cover with an integrally formed explosion-proof valve, characterized in that it includes the following steps in sequence: S1: preparation of raw materials for the top cover; S2: punching a circle of notched explosion-proof valves on a surface of the top cover by a stamping device; S3: cleaning the semi-finished top cover with the explosion-proof valve by a cleaning device; S4: short-time annealing treatment of the cleaned semi-finished top cover by an annealing device.

[0008] The short-time annealing treatment described in the embodiment of the present invention includes the following steps: S41: annealing preparation: check that the annealing equipment is normal, lay a layer of asbestos in a clean annealing basket, and lay a number of integrated top covers flat in the annealing basket; S42: integrated top cover annealing: preheat the annealing equipment to a set temperature value between 300-400°C, and after the temperature is constant, put the annealing basket with the product laid flat in step S41 into the entrance of the annealing equipment, and pass the product through the heat treatment zone through the conveyor belt so that the product is synchronously heated to between 300-400°C, and at the same time, the residence time of the product in the heat treatment zone is controlled between 10-120s; S43: product cooling: the product in step S42 comes out of the heat treatment zone and enters the cooling zone, and the product is cooled to below 100°C at a speed of not less than 20°C / s by the cooling fan, so as to achieve rapid cooling and enter the next process.

[0009] In step S3 of the embodiment of the present invention, cleaning is performed with a cleaning agent at a temperature between 45° C. and 80° C.

[0010] The annealing equipment described in the embodiment of the present invention adopts a continuous annealing furnace.

[0011] In step S42 of the embodiment of the present invention, when the product is conveyed through the heat treatment zone by the conveyor belt so that the product is simultaneously heated to 350° C., the residence time of the product in the heat treatment zone is controlled between 30-120 seconds.

[0012] In step S42 of the embodiment of the present invention, when the product is conveyed through the heat treatment zone by the conveyor belt so that the product is simultaneously heated to 400° C., the residence time of the product in the heat treatment zone is controlled to be between 10 and 20 seconds.

[0013] In step S42 of the embodiment of the present invention, the product is passed through a heat treatment zone by a conveyor belt so that the product is heated to between 300-400° C. at a heating rate of 10-60° C. / s.

[0014] The explosion-proof valve of the embodiment of the present invention comprises a recessed portion extending toward the inner surface of the top cover, the lower edge of the recessed portion is retracted inward to form a convex portion extending toward the outer surface of the top cover, and the notch is arranged on the top surface of the convex portion.

[0015] In the embodiment of the present invention, the top surface of the convex portion is located at a position 10 to 90% between the outer surface of the battery cover and the lower edge of the concave portion.

[0016] The top cover of the embodiment of the present invention has a longitudinal groove extending along its longitudinal axis and extending toward the inner surface of the top cover.

[0017] The longitudinal grooves in the embodiment of the present invention are symmetrically arranged on both sides of the explosion-proof valve; the cross-sectional shape of the longitudinal grooves is approximately V-shaped.

[0018] Compared with the prior art, the present invention has one or more of the following advantages or effects:

[0019] (1) The one-piece stamped explosion-proof valve does not require additional processes for stamping, annealing and welding, which reduces the number of processes, saves costs and improves production efficiency. (2) Through short-term annealing treatment, the material at the notch can be recrystallized and softened, and the structure is more uniform, while the structure of other parts of the top cover remains unchanged. Without changing the overall strength of the top cover, the bursting pressure value is reduced and more stable. (3) The V-shaped structure of the one-piece top cover can effectively reduce the force transmitted to the notch area when the shell cover of the battery cell is subjected to force, thereby stabilizing the bursting pressure value. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 It is a process diagram for preparing the explosion-proof valve and top cover split structure in the existing design.

[0022] Figure 2 It is a process diagram for preparing the explosion-proof valve and top cover integrated structure of the present invention.

[0023] Figure 3 It is a schematic diagram of the short-time annealing process of the present invention.

[0024] Figure 4 It is a front view of the top cover of the integrally formed explosion-proof valve according to an embodiment of the present invention.

[0025] Figure 5 The top cover of the integrally formed explosion-proof valve of the embodiment of the present invention is Figure 4 AA section view in.

[0026] Figure 6 yes Figure 5 A partial enlarged view of the M portion of the top cover of the integrally formed explosion-proof valve of the present invention.

[0027] Figure 7 The top cover of the integrally formed explosion-proof valve in one embodiment of the present invention is a three-dimensional Figure 1 .

[0028] Figure 8 The top cover of the integrally formed explosion-proof valve in one embodiment of the present invention is a three-dimensional Figure 2 .

[0029] Fig. 9 It is a side view of a top cover of an integrally formed explosion-proof valve in one embodiment of the present invention.

[0030] Fig.10 It is a front view of a top cover of an integrally formed explosion-proof valve in one embodiment of the present invention.

[0031] Fig.11 The top cover of the integrally formed explosion-proof valve in one embodiment of the present invention is Fig.10 BB section view in.

[0032] Fig.12 It is the metallographic phase (fibrous structure) diagram of the top cover before annealing of the present invention.

[0033] Fig.13It is the metallographic phase (fibrous structure) diagram of the notched area before annealing of the present invention.

[0034] Fig.14 It is the metallographic diagram of the notched area after annealing at 350°C for different times of the present invention.

[0035] Fig.15 It is the metallographic diagram of the notched area after annealing at 400°C for different times of the present invention.

[0036] Fig.16 The present invention Fig.15 Enlarged view of the metallographic structure of the notched area (local recrystallization occurred) after annealing at 400℃ for 10s.

[0037] Fig.17 It is the metallographic diagram of the notched area after annealing at 450°C for different times of the present invention.

[0038] Fig.18 It is a schematic diagram of the metallographic structure and hardness test part of the top cover of the present invention.

[0039] Figure 19(a) is a metallographic image of the top cover test area after annealing at 350°C for different times.

[0040] Figure 19(b) is a metallographic image of the top cover test area after annealing at 400°C for different times.

[0041] Figure 19(c) is the metallographic image of the top cover test area after annealing at 450°C for different times.

[0042] Fig. 20 It is a hardness change trend chart of the top cover test part after annealing at different temperatures and different times. DETAILED DESCRIPTION

[0043] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively with reference to the relevant drawings. The preferred embodiments of the present invention are shown in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described below. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood. The directions such as "axial direction", "above", "below", etc. in the following text are all for the purpose of more clearly indicating the structural position relationship and are not limitations of the present invention. In the present invention, the "vertical", "horizontal" and "parallel" are defined as: including the situation of ±10% based on the standard definition. For example, vertical usually refers to an angle of 90 degrees relative to the reference line, but in the present invention, vertical refers to the situation within 80 to 100 degrees.

[0044] like Figure 2As shown, the present invention describes a method for processing a top cover with an integrally formed explosion-proof valve, which includes the following steps in sequence: S1: preparation of the raw material of the top cover; S2: punching a circle of notched explosion-proof valves on one surface of the top cover by a stamping device; S3: cleaning the semi-finished top cover with the explosion-proof valve by a cleaning device; S4: short-time annealing treatment of the cleaned semi-finished top cover by an annealing device. Among them, the raw material of the top cover is mainly selected from cold-rolled aluminum strips or cold-rolled aluminum plates (such as: 3003H14 aluminum alloy), and its structure itself is also a fibrous structure with a certain anisotropy, and the shape of the punched explosion-proof valve is elliptical or circular, which will inevitably lead to uneven grain deformation in the notched area along the fiber direction and in the perpendicular fiber direction, and the unevenness of the fiber structure in the notched area of ​​the explosion-proof valve is aggravated during the stamping process. At the same time, the selected thickness is suitable for aluminum strips or aluminum plates between 1.5-3mm. If it is too thick, the integrally stamped explosion-proof valve will find it difficult to break through the scored area of ​​the top cover to release pressure; if it is too thin, the strength of the integrally stamped explosion-proof valve after annealing is low and cannot meet the performance requirements of battery manufacturers. Moreover, the integral stamping thinning amount of the scored area of ​​the middle explosion-proof valve can reach 85%-97% of the thickness of the top cover. Under this large deformation, the material will also harden, which will cause uneven strength in the scored area, and stress concentration is prone to occur at the root of the score, which will eventually result in large fluctuations in the bursting pressure value. In order to solve the problem of uneven metallographic structure and unstable bursting pressure in the scored area of ​​the integrated explosion-proof valve top cover, it is necessary to improve the type of the scored area organization and improve the uniformity of the scored area organization. However, if the integrated explosion-proof valve top cover is annealed for a long time as a whole, it will inevitably lead to a decrease in the overall strength of the top cover and fail to meet the battery cell assembly and working requirements. In order to achieve the effect of only changing the material organization of the notched area of ​​the integrated explosion-proof valve top cover and increasing the plasticity, while not affecting the strength and hardness of other parts of the top cover, the applicant proposed a plan to perform a short-term annealing treatment on the integrated explosion-proof valve top cover to improve the organizational structure of the notched area of ​​the explosion-proof valve and keep the fibrous organization of other parts of the top cover unchanged. On the premise of keeping the overall strength of the top cover unchanged, the material strength of the notched area is reduced, the uniformity of the organization of the notched area is improved, and the bursting pressure value is more stable. Moreover, compared with the split cover plate process, no additional process is required for stamping, annealing and welding of the explosion-proof valve, while saving the mold opening cost of the explosion-proof valve, and the production process is less, saving costs, and greatly improving production efficiency. Furthermore, in step S3, a cleaning agent can also be used for cleaning at 45-80°C to ensure that the effective ingredients of the cleaning agent are fully exerted, while avoiding damage to the metal surface caused by excessive temperature, so that the product is cleaned more cleanly.

[0045] like Figure 3As shown, the short-time annealing treatment includes the following steps: S41: annealing preparation: check that the annealing equipment is normal, lay a layer of asbestos in a clean annealing basket (to avoid scratches on the top cover), and lay several integrated top covers flat in the annealing basket; S42: integrated top cover annealing: preheat the annealing equipment to a set temperature value between 300-400°C, and after the temperature is constant, put the annealing basket with the product laid flat in step S41 into the entrance of the annealing equipment, and pass the product through the heat treatment zone through the conveyor belt so that the product is synchronously heated to between 300-400°C, and at the same time, the residence time of the product in the heat treatment zone is controlled between 10-120s; S43: product cooling: the product in step S42 comes out of the heat treatment zone and enters the cooling zone, and the product is cooled to below 100°C at a speed of not less than 20°C / s by the cooling fan, so as to achieve rapid cooling and enter the next process. Among them, the annealing equipment adopts a continuous annealing furnace to ensure uniform heating of the product, high temperature control accuracy, safety and reliability, and high assembly line operation efficiency. Specifically, the continuous annealing furnace adopts a rotary conveyor belt, and a heat treatment area and a cooling area are set above the conveyor belt. The product to be heat treated is placed on the conveyor belt, first passes through the heat treatment area, and then enters the cooling area. After the product is cooled, it can be loaded into a blister box to realize continuous annealing operation.

[0046] In addition, in the above step S42, the product is conveyed through the heat treatment zone by a conveyor belt to heat the product to between 300-400°C at a heating rate of 10-60°C / s, and then a short-time heat preservation annealing is performed, which can effectively improve the state of the material structure in the notched area, that is, the notched area can obtain fine and uniform recrystallized grains.

[0047] like Figure 4-Figure 6 As shown, the top cover with an integrally formed explosion-proof valve of the present invention comprises: a top cover body 10; an explosion-proof valve 11 integrally formed with the top cover body 10; the top cover body 10 comprises an outer surface 101 and an inner surface 102 opposite to the outer surface; the explosion-proof valve 11 comprises a valve body 111 and a safety notch 112; the valve body 111 also comprises a recess 103 extending toward the inner surface 102 of the top cover body 10, the lower edge 103a of the recess 103 is retracted inward to form a protrusion 104 extending toward the outer surface 102 of the top cover body 10, and the safety notch 112 is arranged on the protrusion 104.

[0048] The cross-sectional shape formed by the concave portion 103 and the convex portion 104 is generally V-shaped, wherein the convex portion 104 is formed in a generally inversely arched shape due to the inward extension of the concave portion 103. The V-shaped structure is used to deform the top cover when it is subjected to force during transportation and battery cell assembly, so as to reduce the force transmitted to the notched area, thereby stabilizing the bursting pressure value.

[0049] See also Figure 6According to one embodiment of the present invention, the distance h1 of the protrusion 104 is less than the distance h2 of the concave portion 103. Optionally, the upper surface of the protrusion 104 is located at 10%-90% of the distance between the outer surface of the top cover body 10 and the lower edge of the concave portion. Optionally, the upper surface of the protrusion 104 is located at 50% of the distance between the outer surface of the top cover body 10 and the lower edge of the concave portion.

[0050] It should be understood that since the safety score 112 is arranged on the top surface of the convex portion 104, its actual position is between the outer surface of the top cover body 10 and the lower edge 103a of the concave portion 103. Therefore, during the stamping process, transportation and cell assembly of the top cover, the external impact force and collision force will be blocked by the outer surface of the top cover body 10 and the lower edge of the concave portion 103 (i.e., the V-shaped area), thereby avoiding potential damage to the fragile safety score 112 area and ensuring the stability of the blasting value.

[0051] like Figure 7-Figure 11 As shown, according to the second embodiment of the present invention, the top cover with an integrally formed explosion-proof valve comprises: a top cover body 10; an explosion-proof valve 11 integrally formed with the top cover body 10; the top cover body 10 comprises an outer surface 101 and an inner surface 102 opposite to the outer surface; the explosion-proof valve 11 comprises a valve body 111 and a safety score 112; the valve body 111 comprises a recess 103 extending toward the inner surface 102 of the top cover body 10, and the safety score 112 is arranged on the bottom surface of the recess 103. The top cover body also comprises a longitudinal groove 113 extending along the longitudinal axis X direction of the top cover body and extending toward the inner surface of the top cover body.

[0052] According to one embodiment of the present invention, the longitudinal grooves 113 are symmetrically arranged on both sides of the valve body 111 along the transverse axis Y. The cross-sectional shape of the longitudinal grooves 113 is substantially V-shaped. The longitudinal grooves are used to deform the top cover when it is subjected to force during transportation and battery cell assembly, so as to reduce the force transmitted to the notched area, thereby stabilizing the bursting pressure value.

[0053] See also Fig.11 According to one embodiment of the present invention, a distance h3 that the longitudinal groove 113 extends toward the inner surface 102 of the top cover body 10 is greater than a distance h4 that the recess 103 extends.

[0054] It should be understood that since the safety score 112 is arranged on the bottom surface of the recess 103, its actual position is between the outer surface of the top cover body 10 and the lower edge 113a of the longitudinal groove 113. Therefore, during the stamping process, transportation and cell assembly of the top cover, the external impact force and collision force will be blocked by the outer surface of the top cover body 10 and the lower edge 113a of the longitudinal groove 113 (i.e., the V-shaped area), thereby avoiding potential damage to the fragile safety score 112 area and ensuring the stability of the blasting value.

[0055] The applicant conducted a bursting pressure test on the top cover with an integrally formed explosion-proof valve of the present invention. The test data is shown in Table 1:

[0056] Table 1 shows the test data of the bursting pressure of the integrated explosion-proof valve cover sample with a notch thickness of 0.22mm. In Table 1, H1 is the thickness of the notch, in mm. C1 is the bursting pressure of the integrated explosion-proof valve cover after punching but not annealing, in MPa. T1, T2, T3, and T4 are the bursting pressure values ​​of the integrated explosion-proof valve cover after punching and annealing at 350℃ / 10s, 30s, 60s, and 120s, in MPa. It can be seen from Table 1 that the maximum burst pressure of the C1 stamping state sample is 4.579MPa, the minimum is 4.359MPa, the average is 4.483MPa, and the standard deviation is 0.096MPa; the average burst pressure of the T1 annealed state sample is 4.121MPa, and the standard deviation is 0.076MPa; the average burst pressure of the T2 annealed state sample is 3.767MPa, and the standard deviation is 0.050MPa; the average burst pressure of the T3 annealed state sample is 3.763MPa, and the standard deviation is 0.045MPa; the average burst pressure of the T4 annealed state sample is 3.755MPa, and the standard deviation is 0.049MPa. It can be seen that after short-term annealing, the burst pressure of the integrated explosion-proof valve top cover is significantly reduced, and the discrete degree of the burst pressure data relative to the average value is reduced, and the burst pressure value is more stable.

[0057] Table 1

[0058]

[0059] In order to further reflect the differences between the top covers of the integrated explosion-proof valves before annealing and after the short-time annealing process, the applicant conducted a comparison through metallographic experiments.

[0060] As a comparative example, Fig.12 As shown in the figure, the metallographic image of the top cover before annealing is a typical fibrous deformation structure. Fig.13 As shown, the metallographic image of the notch area before annealing also belongs to a typical fibrous deformation structure.

[0061] As an example, Fig.14 As shown in the figure, when the temperature of the continuous annealing furnace is controlled at 350℃ and the annealing time is 10s, the metallographic structure of the notch area is still fibrous and no recrystallization occurs; when the product moves forward in the heat treatment zone for 30s, the metallographic structure of the notch area undergoes complete recrystallization to form a recrystallized structure; similarly, when the annealing time is 60s or 120s, complete recrystallization occurs at the notch to form a recrystallized structure.

[0062] like Figure 15-16 As shown in the figure, when the temperature of the continuous annealing furnace is controlled at 400℃ and the annealing time is 10s, recrystallization occurs locally in the notched area; when the product moves forward in the heat treatment zone for 30s, 60s or 120s, the metallographic structure of the notched area undergoes complete recrystallization to form a recrystallized structure.

[0063] like Fig.17 As shown in the figure, when the temperature of the continuous annealing furnace is controlled at 450℃ and the annealing time is 10s, complete recrystallization occurs in the notch area; similarly, when the product moves forward in the heat treatment zone for 30s, 60s or 120s, a complete recrystallization structure is formed in the notch area.

[0064] As shown in Figure 19(a), when the temperature of the continuous annealing furnace is controlled at 350°C, the top cover product as a whole moves forward in the heat treatment zone for 10s, 30s, 60s and 120s, and the top cover structure is still a fibrous structure.

[0065] As shown in Figure 19(b), when the temperature of the continuous annealing furnace is controlled at 400°C, when the top cover product as a whole moves forward in the heat treatment zone for 10 seconds, the top cover structure is still a fibrous structure. When the top cover product is in the heat treatment zone for 30 seconds, 60 seconds and 120 seconds, obvious recrystallization is found in the top cover structure.

[0066] As shown in Figure 19(c), when the temperature of the continuous annealing furnace is controlled at 450°C, when the top cover product as a whole moves forward in the heat treatment zone for 10 seconds, obvious recrystallization is found in the top cover structure. When the top cover product is in the heat treatment zone for 30s, 60s and 120s, obvious recrystallization is also found in the top cover structure.

[0067] like Fig.18 , 20 As shown in the figure, the hardness variation trend of the top cover test part after annealing at different temperatures and different times of the present invention is demonstrated. Fig. 20 The annealing time is taken as the horizontal axis and the Vickers hardness of the top cover is taken as the vertical axis. Fig. 20In the graph, point O marks the hardness of the top cover in the stamped state (i.e. before annealing); points A1 to A4 represent the hardness values ​​after annealing at 350℃ and holding for 10s, 30s, 60s, and 120s, respectively; points B1 to B4 represent the hardness values ​​after the corresponding holding time at 400℃; points C1 to C4 represent the hardness values ​​after the corresponding holding time at 450℃. Fig. 20 It can be seen that when annealed at 350℃, the hardness values ​​of points A1 to A4 decreased slightly compared with point O, but it was not obvious, which indicates that the material mainly experienced a recovery process, and recrystallization has not yet occurred. When the annealing temperature was increased to 400℃, the hardness value of point B1 decreased slightly compared with point O, while the hardness values ​​of points B2 to B4 decreased significantly, indicating that the material had already recrystallized at point B2. When the annealing temperature was further increased to 450℃, the hardness value of point C1 had already decreased significantly compared with point O, and remained stable at points C2, C3, and C4, indicating that the material had already recrystallized at point C1. The hardness change trend is consistent with the changes in the metallographic structure in Figures 19(a), 19(b), and 19(c). In summary, with the increase of annealing temperature, the time for recrystallization of the top cover is significantly shortened.

[0068] In order to achieve the effect of recrystallization in the notch area and non-recrystallization in the top cover area, the temperature and time window should be selected as follows: 350℃ for 30 to 120s, or 400℃ for 10 to 20s. Fig.14 As shown in Figure 19(a), when the temperature is maintained at 350°C for 30 to 120 seconds, the notch is completely recrystallized to form a recrystallized structure, while when the top cover product as a whole moves forward in the heat treatment zone for 10 seconds, 30 seconds, 60 seconds, and 120 seconds, the top cover structure is still a fibrous structure. Figure 15-16 As shown in Figure 19(b), when the temperature is maintained at 400°C for 10 to 20 seconds, recrystallization occurs locally in the notched area, and when the top cover product as a whole moves forward in the heat treatment zone for 10 seconds or 20 seconds, the top cover structure is still a fibrous structure. When the top cover product is in the heat treatment zone for 30 seconds, 60 seconds and 120 seconds, the top cover structure is found to be obviously recrystallized. That is, in step S42, the product is passed through the heat treatment zone by a conveyor belt so that the product is synchronously heated to 350°C, and the retention time of the product in the heat treatment zone is controlled between 30-120 seconds; the product is passed through the heat treatment zone by a conveyor belt so that the product is synchronously heated to 400°C, and the retention time of the product in the heat treatment zone is controlled between 10-20 seconds.

[0069] In summary, through short-time annealing treatment, the material at the notch can be recrystallized and softened, and the structure can be more uniform, while the structure of other parts of the top cover remains unchanged. Under the premise of not changing the overall strength of the top cover, the bursting pressure value is reduced and more stable.

[0070] The above contents described in this specification are merely examples of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, as long as they do not deviate from the contents of the present specification or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for processing a top cover having an integrally formed explosion-proof valve, characterized in that: The following steps are included in sequence: S1: Preparation of raw materials for top cover; S2: An explosion-proof valve having a circle of notches formed on one surface of the top cover by a stamping device; S3: Cleaning the semi-finished top cover with explosion-proof valve by a cleaning device; S4: The cleaned semi-finished top cover is subjected to a short-term annealing treatment through an annealing device.

2. The method for processing a top cover having an integrally formed explosion-proof valve according to claim 1, characterized in that: The short-time annealing treatment comprises the following steps: S41: Annealing preparation: Check that the annealing equipment is normal, lay a layer of asbestos in a clean annealing basket, and lay several integrated top covers flat in the annealing basket; S42: annealing of the integrated top cover: preheat the annealing equipment to a set temperature value between 300-400°C. After the temperature is constant, place the annealing basket with the product laid out in step S41 into the entrance of the annealing equipment, and convey the product through the heat treatment zone via a conveyor belt so that the product is simultaneously heated to between 300-400°C. At the same time, the residence time of the product in the heat treatment zone is controlled between 10-120s. S43: Product cooling: The product in step S42 is taken out of the heat treatment zone and enters the cooling zone. The product is cooled to below 100°C at a speed of not less than 20°C / s by a cooling fan to achieve rapid cooling and enter the next process.

3. The method for processing a top cover having an integrally formed explosion-proof valve according to claim 2, characterized in that: The annealing equipment adopts a continuous annealing furnace.

4. The method for processing a top cover having an integrally formed explosion-proof valve according to claim 2, characterized in that: In the step S42, when the product is conveyed through the heat treatment zone by the conveyor belt so that the product is simultaneously heated to 350°C, the residence time of the product in the heat treatment zone is controlled between 30-120s.

5. The method for processing a top cover with an integrally formed explosion-proof valve according to claim 2, characterized in that: In the step S42, when the product is conveyed through the heat treatment zone by the conveyor belt and the temperature of the product is simultaneously raised to 400°C, the residence time of the product in the heat treatment zone is controlled to be between 10-20s.

6. The method for processing a top cover having an integrally formed explosion-proof valve according to claim 2, characterized in that: In step S42, the product is conveyed through a heat treatment zone by a conveyor belt so that the product is heated to between 300-400°C at a heating rate of 10-60°C / s.

7. The method for processing a top cover with an integrally formed explosion-proof valve according to any one of claims 1 to 6, characterized in that: The explosion-proof valve comprises a concave portion extending toward the inner surface of the top cover, the lower edge of the concave portion is retracted inward to form a convex portion extending toward the outer surface of the top cover, and the notch is arranged on the top surface of the convex portion.

8. The method for processing a top cover with an integrally formed explosion-proof valve according to any one of claim 7, characterized in that: The top surface of the convex portion is located at a position 10 to 90% between the outer surface of the battery cover plate and the lower edge of the concave portion.

9. The method for processing a top cover with an integrally formed explosion-proof valve according to any one of claim 7, characterized in that: The top cover has a longitudinal groove extending along the longitudinal axis direction thereof and extending toward the inner surface of the top cover.

10. The method for processing a top cover with an integrally formed explosion-proof valve according to any one of claims 9, characterized in that: The longitudinal grooves are symmetrically arranged on both sides of the explosion-proof valve; and the cross-sectional shape of the longitudinal grooves is substantially V-shaped.

Citation Information

Patent Citations

  • Novel thermo-mechanical treatment method for improving toughness of 2618 heat-resistant aluminum alloy

    CN102888576A

  • Aluminum alloy sheet for battery lid for molding integrated explosion-proof valve and production method therefor

    CN111094605A

  • Power battery explosion-proof valve with stable structure and machining process thereof

    CN111740065A

  • Aluminum strip material for anti-explosion sheet of energy storing lithium battery and preparation method of aluminum strip material

    CN112779441A

  • Preparation method for integrally forming cover plate and anti-explosion valve

    CN116765208A

Cited By

  • Anti-exposure valve plate, manufacturing method of anti-exposure valve plate, battery shell and manufacturing method of battery shell

    CN119927578A